Trends in racial/ethnic disparities in medical and oral health, access to care, and use of services in US children: has anything changed over the years? - Flores Glenn; Lin Hua (BMC, 2013)
Abstract Introduction The 2010 Census revealed the population of Latino and Asian children grew by 5.5 million, while the population of white children declined by 4.3 million from 2000-2010, and minority children will outnumber white children by 2020. No prior analyses, however, have examined time trends in racial/ethnic disparities in children's health and healthcare. The study objectives were to identify racial/ethnic disparities in medical and oral health, access to care, and use of services in US children, and determine whether these disparities have changed over time. Methods The 2003 and 2007 National Surveys of Children's Health were nationally representative telephone surveys of parents of 193,995 children 0-17 years old (N = 102,353 in 2003 and N = 91,642 in 2007). Thirty-four disparities indicators were examined for white, African-American, Latino, Asian/Pacific-Islander, American Indian/Alaskan Native, and multiracial children. Multivariable analyses were performed to adjust for nine relevant covariates, and Z-scores to examine time trends. Results Eighteen disparities occurred in 2007 for ≥1 minority group. The number of indicators for which at least one racial/ethnic group experienced disparities did not significantly change between 2003-2007, nor did the total number of specific disparities (46 in 2007). The disparities for one subcategory (use of services), however, did decrease (by 82%). Although 15 disparities decreased over time, two worsened, and 10 new disparities arose. Conclusions Minority children continue to experience multiple disparities in medical and oral health and healthcare. Most disparities persisted over time. Although disparities in use of services decreased, 10 new disparities arose in 2007. Study findings suggest that urgent policy solutions are needed to eliminate these disparities, including collecting racial/ethnic and language data on all patients, monitoring and publicly disclosing disparities data annually, providing health-insurance coverage and medical and dental homes for all children, making disparities part of the national healthcare quality discussion, ensuring all children receive needed pediatric specialty care, and more research and innovative solutions.